Covid-19 Detection using qRT-PCR - A Review - Sharma, Yagyavalkya; Sharma, Lalita; Agrawal, Priya; Gupta, Megha; Vardhan, Harsh (Journal for Research in Applied Sciences and Biotechnology, 2022)
In the ongoing Covid pandemic, the monitoring of SARSnCoV-2 with the help of viral loads/viral kinetics has become more essential via the RT-PCR technique. However, the interpretations of qRT-PCR technique results are made as qualitative and quantitative or semi-quantitative, and day by day, this interpretation is becoming more important. Reverse transcription polymerase chain reaction is the most widely used technique for detecting viruses (rRT-PCR). Due to probable false-negative or false-positive findings, present techniques must be improved to avoid incorrect conclusions. Researchers have developed a multiplex rRT-PCR diagnostic method that simultaneously targets viral genes (RdRP and E) and one human gene (RP). The values of the Cycle threshold called Ct values that are a result of the RT-PCR test are highly affected by the variations attained among the different runs required to be operated and must be determined by the laboratories, especially in the quality control of quantitative RT-PCR. Somewhere, batch effects also play an important role in Ct value. Regrettably, several papers on Covid-19 used ingenuous values for Ct from qRT-PCR, which are the incorrect quantitative analysis unit. Qualitative analysis and Quantitative analysis both are of having different meanings; interpretation of Ct values cannot be interpreted directly as viral load; it must need a reference material with standard curves. The tractability and validity of the standard curve are the basis of the evaluation of the values. These factors help attain the accurate quantification of the expected number of viral copies.